Big deal : Bob Fosse and dance in the American musical - Winkler, Kevin (Broadway legacies., 2018)
Bob Fosse is one of the most significant figures in the post-World War II American musical theater. Big Deal: Bob Fosse and Dance in the American Musical is a fascinating look at the evolution of Fosse as choreographer and director. It traces is early dance years, the influence of mentors George Abbott and Jerome Robbins, and the impact of his three marriages-all to dancers-on his career.